SOSYO-KÜLTÜREL BiR TECRÜBE OLARAK TÜRK DIŞ GÖÇÜ: AMERSFOORT (HOLLANDA) ÖRNEGi - Şahin, İıkay (Fırat University, 2009)
This study' alıiıs at investigating tı'ı.e saıİıple of the Turks having left fi·om tı'ı.e town of Bogazliyan and settled in Amersfoorr (Netterlands) as a socio-cultural action creating an irnmigrant socio-cultural life with an intention of permaner.cy and having a design of f\ıture and past. That the experience having begun as a demographic action with an economic motive was turned into iınmigration by the woman and the setian and a_ctor were brought togetlıer will be evaluated_ under the light of data obtained from the sample of the -immigratioiı'-fiorrithe tmVIıicif Bogiızliyan1 towıi.rds Amersfoort. In order to comprehend the experienc_e, ,~f \Jıırr;igrf!P.on and Turkish immigrant society well, 'this srudy considering immigriıfion a'socioci:ultural action assumes an intemally inward ·ıaok asa methodological tendency. Iııstead of separating experience and actor which reflect into acildemi c percejıtioh; such:· an ·approach mentioned above aims at comprehending thoroughly the imrnigration process as the actor's experience and socio-culrural life of the immigrants with all t'!Je basic dynamics. Based on the thçırough interviews and attended observations made in the cantext of Turkish imm i grant society living in Amersfoort, the. transformatinn of a demographic movement into a socio-cuitural ·action in a way. it will create a Turkish immigrant society, and the woman as the essential actor of this transformatian will be revealed.
Turkish Migratian as a Socic-cultural Experience: In the Case of Amersfoort (Nether!ands)
Keywords: Religious Studies; Din Araştırmaları